Contributions towards sustainable cities: urban monitoring and designing tools - Bouillard, Ph.; Athanassiadis, A.; Paolini, F.; Koutra, S.; Galan Gonzalez, A.; Khan, A. Z. (Nazarbayev University, 2014)
The 21st century is the century of cities and urbanization [1]. We live in an increasingly urbanized world where it is projected that by 2050 over 70% of our population will live in cities. The city of the twenty-first century faces major challenges, including social and economic, excessive or even wasteful consumption of resources, transportation congestion, and environmental degradation. In order to address to these critical challenges, an urban renaissance should be founded on principles of sustainable design, economic strength, environmental responsibility, good governance and social well-being [2]. In the current and future research, three elements will be investigated: (i) understanding the consumption and functioning of cities through multi-scalar monitoring systems (ii) improving the air quality and reducing the carbon footprint of cities (iii) and the design of optimal green transportation systems.
Keywords: 21st century; designing tools; economic; environmental responsibility; sustainable design; monitoring systems